(untitled) (Konferensiyalar | Conferences, 2024)
This thesis investigates the impact of ethnic and cultural factors on modern teacher education, employing a comparative analysis of regional, national, and international experiences. It argues that increasing student diversity necessitates a shift towards culturally responsive pedagogy and inclusive learning environments within teacher education programs. The study examines key areas such as addressing the representation gap in the teaching profession, navigating linguistic diversity, and fostering intercultural competence and global citizenship among future educators. By drawing on diverse models and best practices, the thesis proposes recommendations for building a more equitable and inclusive education system that effectively prepares teachers to meet the needs of all learners in the 21st century.